Proceedings of the 8th International Conference of Asian Association of Indigenous and Cultural Psychology (ICAAIP 2017) 2018
DOI: 10.2991/icaaip-17.2018.42
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning for Teachers Training in Indonesia: The Potential of Mobile Phones as the Device

Abstract: Abstract-This paper presents a review on mobile phones, from an Indonesian perspective to investigate the prospect of using mobile phones for mobile learning based training. The review revealed the potential of mobile phones, compared to other mobile devices, to be used as the primary tool in a mobile learning system. In Indonesia, mobile phones are used extensively, and the price for devices and services are affordable for Indonesians. The broad coverage area of the mobile network was also a reason to choose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In addition, the researchers believe that mobile learning is commenced with the aim to enhance students learning experience, and not to be used for as primary method to provide the entire course. Now the main difference can be seen between mobile learning and e-learning, through mobile learning one can easily educate him/herself at any time (Yusri et al, 2017;García-Martínez et al,2019;Suner et al 2019;Saroia, & Gao, 2019) and any place whereas in e-learning one must have a computer or laptop, the drawback of e-learning is that it needs privacy as well as separate place and may there is chance that PCs and laptop are not allowed somewhere, then it became difficult for the user to retrieve the required information at that time (Wang et al, 2009).…”
Section: Mobile Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the researchers believe that mobile learning is commenced with the aim to enhance students learning experience, and not to be used for as primary method to provide the entire course. Now the main difference can be seen between mobile learning and e-learning, through mobile learning one can easily educate him/herself at any time (Yusri et al, 2017;García-Martínez et al,2019;Suner et al 2019;Saroia, & Gao, 2019) and any place whereas in e-learning one must have a computer or laptop, the drawback of e-learning is that it needs privacy as well as separate place and may there is chance that PCs and laptop are not allowed somewhere, then it became difficult for the user to retrieve the required information at that time (Wang et al, 2009).…”
Section: Mobile Learningmentioning
confidence: 99%
“…Similarly researchers (Tang et al, 2017) says that the use of mobile technology for education purpose (Khan et al, 2018;Suner et al 2019;Saroia, & Gao, 2019;Nikolopoulou, 2018;Bai., 2019) or training purpose (Yusri, Goodwin, & Mooney, 2017;García-Martínez, Fernández-Batanero, Cobos Sanchiz, & Luque de La Rosa, 2019) gaining much consideration. All these advancement from education to changing the environment of training system is known as e-learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of mobile devices for interaction and communication is uniquely more pervasive and extensive where the vast majority of Internet users (85%) in Indonesia conducting online activities using their mobile phones ("In Indonesia", 2015). A recent study on the potential of mobile phones for teacher training in Indonesia indicated that the price for devices and services was affordable and the coverage area of the mobile network was broad, and this is the reason why it has become the preferred mobile learning device (Yusri, Goodwin, & Mooney, 2018). According to a study on Global Mobile Behaviour by Millward Brown, Indonesians spend nearly five hours a day on a smartphone, more than any other nationality (Southgate, 2014).…”
Section: Internet Connectivity and Technology Infrastructurementioning
confidence: 99%
“…In the Indonesian context, mobile technology and social media are popular communication platforms among teachers and teacher educators, which can offer potential affordances for professional learning (Sari, 2012). The vast majority of Internet users in Indonesia (85%) conduct online activities using their mobile phones ("In Indonesia", 2015) and mobile phones are more preferable for teacher training in Indonesia because the price for devices and services were affordable and the coverage area of the mobile network was broad (Yusri et al, 2018). The affordability of using mobile technology allows "access to Internet resources, run experiments in the field, capture, store and manage everyday events as images and sounds and communicate and share the material with colleagues and experts around the world" (Sharples, 2002, p.222).…”
Section: Collaborative and Leader-driven Group Behavioursmentioning
confidence: 99%